Web2forDev: A problem shared - Watley, Crystal; Mubendo, Collins (Technical Centre for Agricultural and Rural Cooperation, 2007)
Introducing technology to rural areas can be difficult. But networking and sharing ideas has provided solutions for one village in western Kenya, where a group of women is now learning how to use a computer. The next step is to learn about web 2.0.